Indeks Glikemik Nasi Putih dengan Beberapa Cara Pengolahan: Glycemic Index of Rice by Several Processing Methods - Purbowati Purbowati; Isti Kumalasari (Universitas Airlangga, 2023)
Background: In diabetes mellitus patients, one of the efforts to control normal blood glucose levels is to eat low glycemic index foods. Rice is an Indonesian staple food that contains carbohydrates. Several methods of processing could affect the glycemic index of rice. Objectives: To analyze the glycemic index of rice processed by several methods. Methods: The design used was quasi-experimental. A total of ten people with criteria of healthy, aged 19-29 years, having normal body mass index and blood glucose levels were used in this study. Subjects were given five treatments. Treatment: 1) was given glucose as a reference, 2) was given rice that was traditionally processed and just cooked, 3) was given rice that was traditionally processed and had been stored at room temperature (25°C) for 12 hours, 4) was given rice that was electronically processed and just cooked, and 5) was given rice that was processed in a modern way and had been stored for 12 hours in magic com at hot temperature. Among the treatments, there was a gap of 7 days. Results: Traditionally processed rice has a glycemic index of 21.6, increasing to 24.7 after being stored at room temperature for 12 hours. Meanwhile, processed electronic rice has a glycemic index of 22.9 and increases to 36,4 after being stored in a rice cooker (hot temperature) for 12 hours. Conclusions: The four rice groups processed by various methods had low glycemic index values. Rice stored for 12 hours had a higher glycemic index value than freshly cooked rice.